Influence of anaerobic physical effort in the horizontal and vertical peripheral view - M. Arteaga; D. Cárdenas; M. Delgado (Asociación Española de Ciencias del Deporte, 2010)
There now seems to be a generalized tendency to consider that sporting performance declines as the sportsperson becomes fatigued. However, there is little empirical evidence to show that this adversely affects visual function. In some sports it is necessary to see stimuli in zones peripheral to central vision. The aim of this study is to analyze the influence of anaerobic exertion on vertical and horizontal Peripheral Vision. An intra-subject design was used with 14 replications. The visual parameters of Vertical Peripheral Vision and Horizontal Peripheral Vision were measured in different fatigue conditions to analyze the possible negative influence which this could exert on the subject's visual capacity. The results show that fatigue due to anaerobic effort does not harm the visual abilities studied. KEY WORDS: Peripheral Vision, Fatigue, Anaerobic exertion, Visual abilities